Natural Fiber Based Composites II - Evon, Philippe (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Over the last twenty years, the use of cellulosic and lignocellulosic agricultural by-products for composite applications has been of great interest, especially for reinforcing matrices. Fibers of renewable origin have many advantages. They are abundant and cheap, have a reduced impact on the environment, and are independent from fossil resources. Their ability to mechanically reinforce thermoplastic matrices is well known, as is their natural heat insulation ability. The matrices can themselves be of renewable origin (e.g., proteins, thermoplastic starch, poly(lactic acid), polyhydroxyalkanoates, etc.), thus contributing to the development of 100% bio-based composites with a controlled end of life.This Special Issue, "Natural Fiber Based Composites", provides an inventory of the latest research in the area of composites reinforced with natural and wood fibers, focusing particularly on the preparation and molding processes of such materials (e.g., extrusion, injection molding, hot pressing, 3D printing, etc.) and their characterizations. It contains one review and ten research reports authored by researchers from three continents and eleven countries, namely China, Egypt, France, Germany, Italy, Malaysia, Poland, Russia, Saudi Arabia, Tunisia, and Yemen.